The Influence of Organizational Communication Climate on Cisral Library Performance in Padjadjaran University - Rika Jufriazia Manita; Benni Handayani; Oktri Permata Lani (UIR Press, 2020)
This research raised about the effect Organizational Communication Climatic of CISRAL’s Library Performance at the University of Padjadjaran, and also tells about every point of the indicator: trust, participatory decision making, openness in communication, listening in communication up to and think about the goals of high-performance. This research use survey descriptive and quantitative survey explanatory with path analysis which is used to determine the influence of the independent variable of organizational communication climate dimensions (X) with the confidence indicator, participatory decision making, openness in communication, listening in communication up to and think about goals high performance to the performance of the library (Y). Based on the results of this study can be concluded the discussion of organizational communication climate influence directly and indirectly to the performance of the library at the University of Padjadjaran CISRAL.